Designing and organizing the components of achievement files for applied art education students (Al-Academy, 2025)
Achievement files are one of the alternative assessment formats that have become used in many developed and developed institutions and countries recently, as they focus on important learning processes that can be developed within the framework of school work and outside it, and identifying learning needs. The research aims to reveal the design and organization of the achievement files of applied art education students according to the evaluation criteria. The research procedures were represented by the descriptive analytical method. The research sample was chosen in a (random) manner because it is consistent with... With the research problem and its objectives. The researcher approved. On the indicators of the theoretical framework in building the research tool.Among the most important results reached by the researcher: Evaluation helps build an educational program, evaluate its achievements, and improve its effectiveness, as it helps teachers and learners improve teaching and learning. Among the conclusions reached by the researcher: adopting achievement files in the educational process contributes to developing students’ educational skills. Among the research recommendations: preparing a training program related to the use of achievement files for educational supervisors and implementing it for training courses during the summer vacation.